The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1016/s1097-2765(00)80361-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase ε Catalytic Domains Are Dispensable for DNA Replication, DNA Repair, and Cell Viability

Abstract: DNA polymerase epsilon (Pol epsilon) is believed to play an essential catalytic role during eukaryotic DNA replication and is thought to participate in recombination and DNA repair. That Pol epsilon is essential for progression through S phase and for viability in budding and fission yeasts is a central element of support for that view. We show that the amino-terminal portion of budding yeast Pol epsilon (Pol2) containing all known DNA polymerase and exonuclease motifs is dispensable for DNA replication, DNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
249
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(273 citation statements)
references
References 30 publications
20
249
2
Order By: Relevance
“…Recently, we have shown that the DNA polymerase and exonuclease domains of Pol ⑀ are dispensable for cell viability in fission yeast (Feng and D'Urso, 2001). Similar observations have been made for the evolutionarily distant yeast, Saccharomyces cerevisiae (Kesti et al, 1999;Dua et al, 2000). These findings have raised important questions regarding the essential role of this replicative enzyme in DNA synthesis.…”
Section: Introductionsupporting
confidence: 66%
“…Recently, we have shown that the DNA polymerase and exonuclease domains of Pol ⑀ are dispensable for cell viability in fission yeast (Feng and D'Urso, 2001). Similar observations have been made for the evolutionarily distant yeast, Saccharomyces cerevisiae (Kesti et al, 1999;Dua et al, 2000). These findings have raised important questions regarding the essential role of this replicative enzyme in DNA synthesis.…”
Section: Introductionsupporting
confidence: 66%
“…The polymerase activity of E. coli DNA polymerase I is not essential, but the unique 5Ј-3Ј exonuclease activity is essential, being required to remove the RNA from the ends of Okazaki fragments (63). Eukaryotic Pol ⑀ is essential, but one report on this subject indicates that the region encoding the polymerase activity is dispensable (64). Despite these arguments, DnaE could still be the lagging strand polymerase and thus reflect major differences and requirements between Gram-positive and Gram-negative cells.…”
Section: Does Dnae Function At the Replicationmentioning
confidence: 99%
“…As pol epsilon possesses a relatively high processivity, it is now widely accepted that in eukaryotic cells pol delta and epsilon are responsible for the lagging-and leading-strand synthesis, respectively, 19 although pol epsilon has been demonstrated not to be essential in yeast. 20 The catalytic subunits of pol delta and epsilon, for example, p125 [21][22][23] and p261 24,25 in mammals, include the 3¢ exonuclease, that is, proofreading, domains. Indeed, in the yeast mutants in which pol delta or epsilon proofreading is selectively inactivated, the mutations rates are 10-100 times higher than the wild-type strains.…”
Section: Introductionmentioning
confidence: 99%